Project on Human Development in Chicago Neighborhoods (PHDCN): Infant Assessment Unit, Wave 1, 1995-1997 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. Part of the Longitudinal Cohort Study was the Infant Assessment Unit (IAU). The objective of the IAU was to observe how prenatal and postnatal conditions affect the health and cognitive functioning of infants during the first year of life. Consisting of several instruments, the IAU sought to measure infant cognition and quantify the experiences of the sampled infants from Cohort 0 during their first 12 months of life. Additionally, the IAU examined the circumstances surrounding the mother's pregnancy and the subsequent care received by the infant.